The diversity and use of ritual plants by the Alas tribe in Babul Rahmah sub-district, Southeast Aceh, Indonesia - Sari, Nonika; Suwardi, Adi Bejo; Indriaty, Indriaty (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This study aims to identify the diversity of plant species used in traditional ceremonies of the Alas tribe in Babul Rahmah District, Southeast Aceh Regency, Aceh, Indonesia. The Alas tribe’s cultural practices are deeply intertwined with the use of plants in rituals such as pesijuk, tepung tawar, majun, and kendukhi khak-khak. Using a descriptive qualitative method, data were collected through field observations and semi-structured interviews with 155 informants, aged 16 to 70, selected through purposive sampling. The informants included elders, religious leaders, and community members knowledgeable about local traditions. The results identified 35 plant species from 21 families used in traditional ceremonies, with Cocos nucifera (coconut) and Areca catechu (betel nut) from the Arecaceae family being the most prominent. These plants hold symbolic significance, representing purification, life, and honor in ritual contexts. Additionally, species from the Zingiberaceae family, such as Zingiber officinale (ginger) and Curcuma longa (turmeric), are frequently used in majun ceremonies for spiritual purification and protection. The study also highlighted a decline in ethnobotanical knowledge among younger generations, with only 40% of informants aged 16–30 demonstrating extensive knowledge of the plants used in ceremonies, compared to 85% among those aged 50 and above. This decline is largely due to modernization and the lack of integration of traditional knowledge into formal education. The research underscores the importance of preserving ethnobotanical knowledge through collaboration between traditional institutions and educational bodies, emphasizing the role of tradition-based education in mitigating the loss of cultural heritage.